Using established predictors of post-traumatic stress to explain variations in recovery outcomes among orthopedic patients. (October 2015) - Cremeans-Smith, Julie K; Contrera, Kevin; Speering, Leann; Miller, Eric T; Pfefferle, Kiel; Greene, Kenneth; Delahanty, Douglas L
The present studies examine whether information contained in medical records can be used to predict outcomes following two orthopedic procedures: repair of hip fracture and total knee replacement. Study 1 reports the acute, in-hospital recovery data from the medical records of 119 hip fracture patients. Study 2 is a prospective, longitudinal investigation of 3-month postoperative recovery of 110 total knee replacement patients. Patients characterized by a greater number of post-traumatic stress risk factors experienced poorer outcomes following orthopedic surgery. Our results suggest that patients at risk for negative outcomes can be identified by information readily available to medical personnel.